Korelasi Terapi Okupasi pada Anak Prasekolah dengan Kecanduan Gadget di Wilayah Komplek Dewa Ruci Kota Cirebon - Meristika Rachman, Sylvia; Iryadi, Roni; Noorlinda, Noorlinda; Atma Battya, Annesya (Jurnal Kesehatan Pertiwi, 2025)
Background: The quality of child growth and development is influenced by health and nutrition, education and child welfare, the environment in which children grow and develop, as well as other contributing factors. One of the factors related to the quality of child development is technology. Objective: The aim of this study was to determine the correlation between occupational therapy in preschool children and gadget addiction in the Dewa Ruci Complex, Cirebon City. Methods: This research employed a quantitative approach with a correlational analytic design using a cross-sectional method. The study was conducted in June 2025. The study population consisted of preschool children aged 3–6 years living in the Dewa Ruci Complex, Cirebon City. A total of 35 respondents were included as the sample.Results: The findings revealed that among 35 respondents, the majority exhibited high levels of gadget addiction, totaling 29 children (82.8%). Furthermore, most preschool children who had undergone occupational therapy also showed high levels, totaling 33 children (94.3%). The p-value obtained was 0.000034 < 0.05, indicating that H1 was accepted. Conclusion: There is a significant relationship between occupational therapy in preschool children and gadget addiction in the Dewa Ruci Complex area.